Adamanthinone of the tibia - Plaza C., Jaime; Sánchez S., Jaime; Barredo B., Ramón; Marengo B., Carlos (Revista Universidad de Guayaquil, 1990)
Adamantinoma of the Tibia is a relatively rare tumor; At the moment, almost 250 cases have been reported in the world literature, many of which have been reconfirmed by subsequent histological studies. This is a tumor whose histological characteristics are similar to ameloblastoma of the jaw, having a similar biological behavior, which is why it is considered to have its origin in the same embryonic carray, that is, in the endoderm.